Scene design and stage lighting - Parker, W. Oren 4 0 (Wilford Oren)16; Wolf, R. Craig,;Block, Dick; 5 (South Melbourne, Victoria, Australia Thomson/Wadsworth, 2003)
Presents a guide to scene design and stage lighting for the theater, looking at different venues, reviewing the elements of design and composition, exploring the design process, discussing scene construction, examining sound design and systems, and describing the elements of stage lighting.
Includes bibliographical references (p. 633-636) and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Stage-setting and scenery. -- Theaters;Stage lighting. -- 20; 20; 2